Analysis Region Capacity Levels in the Face Tsunami in Lebak Regency of Banten - muzani, Muzani; Setiawan, Cahyadi; Fauziah, Syifa (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
This study aims to determine the capacity of the Bayah coastal area in dealing with the tsunami disaster. The research method used in this research is descriptive method. This study is a population study consisting of 4 villages, including Sawarna Village, East Sawarna Village, West Bayah Village, and Darmasari Village. The unit of analysis in this study is the region. In this study the instrument used was a questionnaire as a guide to interview respondents who represented the area under study. The assessment of regional capacity in disaster management is carried out by looking at the four priorities of disaster risk reduction programs. These priorities are adopted in the Hyogo Framework for Action (KAH). With the following priorities: 1). Disaster education 2). Early warning and disaster risk assessment 3). Reduction of basic risk factors 4). Development preparedness on all lines. The results of this study indicate that the Bayah Coast region in the face of tsunamis has a low capacity of 18.7% which falls into the level 1 category. The area has had small achievements in disaster risk reduction efforts by implementing several advanced actions in plans or policies . This shows that the regional capacity in implementing disaster management is still very lacking, requiring intensive capacity building. Keywords: Capacity, Hyogo Framework for Action, Tsunami